Latin for All Identities - Bethanie Sawyer (The Journal of Classics Teaching, 2016)
It is commonly known that in Latin, the verb that means to teach (docere) takes a double accusative: you teach a subject and a student. After a Master's degree and 12 years of teaching at the secondary level, I feel like I am pretty good at teaching my subject. But what I have come to realise is that the Latin teacher training program I graduated from did not prepare me quite so well as to teach my students – in the sense that there was a very important aspect of teacher training missing from my program and, as far as I knew, every other program out there. I never formally learned the importance of an inclusive and affirming classroom and curriculum, or how to achieve it.